Emotional, physiological, biochemical, and behavioral responses to acute stress and uncertainty in military personnel. - Julie A Cantelon; Ester Navarro; Tad T Brunyé; Marianna D Eddy; Nathan Ward; Ida Pantoja-Feliciano; Jordan Whitman; Manob Jyoti Saikia; Grace E Giles (PLoS ONE)
Stress carries diverse implications for perceptual, cognitive, and affective functions. One population particularly susceptible to acute stress-induced cognitive changes are individuals with high-stress jobs (e.g., military personnel). These individuals are often tasked with maintaining peak cognitive performance, including memory, spatial navigation, and decision-making under threatening and uncertain conditions. Previous research has separately examined decision-making under conditions of stress or uncertainty (i.e., ambiguous discrimination between friends and foes). However, questions remain about how operationally relevant stress impacts memory encoding and recall, or spatial learning, as well as how uncertainty may impact decision-making during stress. To address this gap, we examined the influence of a military-relevant emotional stressor on a series of cognitive tasks including recognition memory task (RMT), spatial orienting task (SOT), and shoot/don't shoot decision making (DMT). To examine the effects of uncertainty and stress we varied the stimulus clarity in the DMT. We utilized threat of shock (TOS) as a high-stakes outcome for decision errors. TOS increased sympathetic arousal but did not affect subjective emotional or HPA responses. TOS influenced decision times and confidence ratings in the DMT, but not response sensitivity or response bias. DMT performance varied by stimulus clarity (uncertainty) but did not differ between stress conditions. TOS did not influence recognition memory or spatial orienting. In sum, high levels of stress and uncertainty characterize military operations, yet stress experienced in military contexts can be difficult to induce in laboratory settings. We discuss several avenues for future research, including methodological considerations to better assess the magnitude and specificity of emotional stress-induction techniques in Soldiers.